THE ROLE OF FAMILY INTERVENTION IN EARLY DETECTION OF CONGENITAL DEAFNESS: A CASE STUDY - Alif Sholehen; Fajrinka Pralampito; Antonius Galih; Akbar Ghaus; Andi Airina; Nyilo Purnami (Journal of Community Medicine and Public Health Research)
Congenital deafness is a hearing loss disorder that occurs at birth and is one of the disorders that can cause complications when it is not treated.1 Children with hearing loss will face difficulties such as poor development outcomes, including poor speech and language skills and face difficulties with cognition and social-emotional interactions. Early intervention has been proven to be one of the most important factors leading to good outcomes for children with congenital hearing loss.2 This case study is intended to highlight the importance of early case detections, early interventions and how family support plays a crucial role in the development of children with hearing loss. With the support of her family, Ms. DRP has gone through several speech and hearing therapies since her surgery and has proven to have an above-average linguistic abilities, showing that early problem detection does not hinder the development and achievement of children with congenital hearing loss.